2014
DOI: 10.1088/0031-9155/59/6/1501
|View full text |Cite
|
Sign up to set email alerts
|

Use of articulated registration for response assessment of individual metastatic bone lesions

Abstract: Accurate skeleton registration is necessary to match corresponding metastatic bone lesions for response assessment over multiple scans. In articulated registration (ART), whole-body skeletons are registered by auto-segmenting individual bones, then rigidly aligning them. Performance and robustness of the ART in lesion matching were evaluated and compared to other commonly used registration techniques. Sixteen prostate cancer patients were treated either with molecular targeted therapy or chemotherapy. Ten out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Lesion contours on PET/CT images were verified by an experienced nuclear medicine physician, and contours smaller than 1.5 cm 3 as measured by PET volume were excluded. Corresponding lesions were automatically matched between paired scans using articulated registration (20).…”
Section: Roi Definitionmentioning
confidence: 99%
“…Lesion contours on PET/CT images were verified by an experienced nuclear medicine physician, and contours smaller than 1.5 cm 3 as measured by PET volume were excluded. Corresponding lesions were automatically matched between paired scans using articulated registration (20).…”
Section: Roi Definitionmentioning
confidence: 99%
“…The number of eligible studies increased over time, indicating a growing interest in the subject of automated analysis of tumor burden ( Figure 1 ). Most single-institution studies (n = 9/25, 36%) originated from the United States; moreover, most of the multi-institutional studies included an American center (n = 6/9, 67%) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Five studies originated from Germany [ 23 , 24 , 25 , 26 , 27 ], four from Sweden [ 28 , 29 , 30 , 31 ], and six from Japan [ 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to overcome the limitations of uptake threshold techniques, hybrid analysis techniques have been developed in the last few years [ 13 , 16 , 17 , 23 , 26 ]. These methods are applied to multi-modal imaging (PET/CT or SPECT/CT) and use the information from both the morphologic and the functional dataset to define the tumor volume accurately.…”
Section: Resultsmentioning
confidence: 99%
“…An experienced nuclear medicine physician reviewed lesion contours on the PET/CT images to confirm all non-disease uptake was excluded from analysis. Employing hybrid PET/CT segmentation and articulated skeletal-registration (Yip et al , 2014), bone lesions were identified and tracked across scans to allow for response assessment (Yip and Jeraj, 2014). Articulated registration employs a piece-wise rigid registration of skeletal bones from CT and applies transformations to bones and lesions from PET/CT.…”
Section: Methodsmentioning
confidence: 99%